Coronavirus disease 2019 (COVID-19) in domestic animals and wildlife: advances and prospects in the development of animal models for vaccine and therapeutic research. Issue 12 (1st December 2020) - Sharun, Khan; Tiwari, Ruchi; Patel, Shailesh Kumar; Karthik, Kumaragurubaran; Iqbal Yatoo, Mohd; Malik, Yashpal S.; Singh, Karam Pal; Panwar, Parmod Kumar; Harapan, Harapan; Singh, Raj Kumar; Dhama, Kuldeep
ABSTRACT: SARS-CoV-2, which causes coronavirus disease 2019 (COVID-19), is suspected to have been first contracted via animal-human interactions; it has further spread across the world by efficient human-to-human transmission. Recent reports of COVID-19 in companion animals (dogs and cats) and wild carnivores such as tigers have created a dilemma regarding its zoonotic transmission. Although in silico docking studies, sequence-based computational studies, and experimental studies have shown the possibility of SARS-CoV-2 infection and transmission in cats, ferrets, and other domestic/wild animals, the results are not conclusive of infection under natural conditions. Identifying the potential host range of SARS-CoV-2 will not only help prevent the possibility of human-to-animal and animal-to-human transmission but also assist in identifying efficient animal models that can mimic the clinical symptoms, transmission potential, and pathogenesis of the disease. Such an efficient animal model will accelerate the process of development and evaluation of vaccines, immunotherapeutics, and other remedies for SARS-CoV-2.